Perianal panfistulosis About a case - Montano, Daniel; Villanueva, Oscar; Campos, Alejandro; Varela, Daniel (Cirugía del Uruguay, 2004)
The authors present a case with mu/tiple complicated anorectal fistulas. lt is a rare type and diagnosis and treatment involve specific aspects that have to be taken into account. Given the limitations of preoperative clínica/ assessment, severa/ diagnostic procedures have been suggested to aid the surgeon during preoperative evaluation. The paper refers to the ana/ysis of anatomic and pathologic aspects to be eva/uated prior to and during surgica/ treatment.